ANALISIS PUTUSAN MAHKAMAH KONSTITUSI NO. 68/PUU/XII/2014 KAITANNYA DENGAN NIKAH BEDA AGAMA MENURUT HUKUM ISLAM DI INDONESIA - Islamiyati, Islamiyati (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2017)
Background research originated from the Constitutional Court decision No. 68/PUU / XII /2014 rejected the application for judicial review of material (judicial review) Article 2 Paragraph (1) of the Constitution NRI UUP 1945. The goal is to analyze the legal considerations of the decision of the judge of the Constitutional Court No. 68/PUU/XII/2014 and its legal consequences. The judge rejected the applicant because it contradicts the principle of the Godhead, moral values, culture and principles of marriage law in Indonesia. The existence of Islamic law can be reestablished by the interpretation of Article 2 Paragraph (1) UUP properly and constitutionally. The role of the Constitutional Court decision has correlate between religion and state laws are harmonized, and can enforce Islamic law which is based on maqÄá¹£id al-sharÄ«â€™ah.[]Latar belakang penelitian berawal dari putusan MK No. 68/PUU/XII/2014 yang menolak permohonan uji materiil (judicial review) Pasal 2 Ayat (1) UUP terhadap UUDÂ 1945. Tujuannya untuk menganalisis pertimbangan hukum putusan hakim MK No. 68/PUU/XII/2014 dan akibat hukumnya. Hakim menolak permohonan pemohon karena bertentangan dengan prinsip Ketuhanan, nilai moral, budaya dan prinsip hukum perkawinan di Indonesia. Eksistensi hukum Islam dapat ditegakkan kembali oleh penafsiran Pasal 2 Ayat (1) UUP secara benar dan konstitusional. Peran putusan MK telah mengkorelasikan antara hukum agama dan negara yang harmonis, serta dapat menegakkan hukum Islam yang berpijak pada maqÄá¹£id al-sharÄ«â€™ah.